Stable isotope evidence for trophic niche partitioning in a South African savanna rodent community. Issue 3 (1st June 2015) - Codron, Jacqueline; Duffy, Kevin J; Avenant, Nico L; Sponheimer, Matt; Leichliter, Jennifer; Paine, Oliver; Sandberg, Paul; Codron, Daryl
Abstract: Species' partitioning of resources remains one of the most integral components for understanding community assembly. Analysis of stable carbon and nitrogen isotopes in animal tissues has the potential to help resolve patterns of partitioning because these proxies represent the individual's diet and trophic niche, respectively. Using free-ranging rodents in a southern African savanna as a model community, we find that syntopic species within habitats occupy distinct isotope niches. Moreover, species with strongly overlapping isotope niches did not overlap in their spatial distribution patterns, suggesting an underlying effect of competitive exclusion. Niche conservatism appears to characterize the behaviour of most species in our sample - with little or no observed changes across habitats - with the exception of one species, Mastomys coucha . This species displayed a generalist distribution, being found in similar abundances across a variety of habitats. This spatial pattern was coupled with a generalist isotope niche that shifted across habitats, likely in response to changes in species composition over the same spatial gradient. The case for M. coucha supports contentions that past competition effects played a significant evolutionary role in shaping community structures of today, including the absence of strong interspecific niche overlaps within particular habitats. Our study highlights the value of stable isotope approaches to help resolve key questions in community ecology, and moreover introduces novel analytical approaches to quantifying isotope niche breadths and niche overlaps that are easily comparable with traditional metrices.